Whole‐Cell‐Mimicking Carrier‐Free Nanovaccines Amplify Immune Responses Against Cancer and Bacterial Infection. (23rd November 2021) - Qin, Ming; Du, Guangsheng; Qiao, Nan; Guo, Zhaofei; Jiang, Min; He, Chunting; Bai, Shuting; He, Penghui; Xu, Yanhua; Wang, Hairui; Gong, Tao; Zhang, Zhirong; et al.
Abstract: Whole‐cell vaccines that provide broad‐spectrum antigens have been explored for recent decades. But so far, they have revealed limited success in clinical trials, possibly owing to their inefficiency in targeting immune organs and antigen‐presenting cells (APCs). Herein, a facile strategy is developed to convert the whole‐cell vaccines into the nanoscale size to promote their lymphatic migration and subsequent intracellular antigen presentation to maximize immune responses. Briefly, the study designs a multiple antigen delivery platform based on alum‐induced and cancer/bacterial cell membrane coated protein antigen nanoparticles. Through a simple two‐step vortex‐sonification method, a universal carrier‐free nano‐vaccine without additional excipients could be quickly fabricated. After subcutaneous vaccination, the developed nanovaccines rapidly migrate to lymph nodes, leading to their effective uptake by lymph node‐resident APCs, and subsequent antigen presentation and activation of downstream immune processes. Overall, the described promising work offers a safe, effective, facile, and widely applicable vaccine strategy, which has great potential for clinical transformation. Abstract : The text reports a universal carrier‐free nano‐vaccine that utilizes the unique advantages of biological membrane and the strong interaction between protein antigens and aluminum. These designed nanovaccines can effectively migrate to lymph nodes and potently induce adaptive immune responses, thereby significantly delaying tumor growth or improving the survival rate of mice after lethal bacterial infection.